Growth of micro and small scale enterprises and its driving factors: empirical evidence from entrepreneurs in emerging region of Ethiopia - Hayelom Abrha Meressa (Journal of Innovation and Entrepreneurship, 2020)
Purpose: The purpose of this study was to examine micro and small scale enterprises' growth determinants operating in Benishangul-Gumuz Regional State of Ethiopia as emerging region. Design/methodology/approach: The study adopted an explanatory research design with arrangement of primary data collection via a cross-sectional survey questionnaire followed by mixed research approach. The sample of this study was 220 enterprises determined by Yamane's formula and selected using proportional stratified random sampling technique. Findings: The result of regression analysis revealed that initial investment, access to land, access to finance, location, sectoral engagement, market linkage, and business experience are significant in explaining growth in one hand. On the other side, however, gender, education, ownership, formal recording, and financial management practice are found to be insignificant variables in determining enterprises' growth. Research limitations/implications: More evidence is needed on micro and small scale enterprises' growth determinants before any generalization of the results can be made. In addition, the empirical tests were conducted only on 220 entrepreneurs since 2018. Therefore, the results of the study cannot be assumed to extend beyond this group of entrepreneurs to different study periods. Practical implications: The study might help the entrepreneurs in addressing the factors affecting growth to take actions toward developing their performance and in turn contribute to employment, export participation, poverty alleviation, and women empowerment. Originality/value: This paper adds to the literature on the determinants of microand small-scale enterprises' growth. In particular, it tests the impact of initial investment, access to land, access to finance, location, sectoral engagement, market linkage, business experience, education, ownership structure, and financial management practice on growth of enterprises.
Keywords: 650; Assosa Zone; Constraints; Growth; Micro and Small Enterprises